The role of CD4 and CD8 lymphocytes and macrophages in psoriasis vulgaris - Čabrijan, Leo (Array, 2009)
Summary: Current knowledge of the immunopathogenesis of psoriasis vulgaris is based on the crucial role of CD4 and CD8 lymphocytes. Also, the connection of activated lymphocytes with macrophages, especially dendritic cells and plasmacytoid dendritic cells, is considered to be significant. In the present study, the expression of CD4+ lymphocytes as well as CD8+ lymphocytes (P<0.001) and macrophages (P<0.001) was found to be significantly increased in lesional skin epidermis and dermis in psoriasis vulgaris patients as compared with healthy skin. These findings suggested a cascade or chain reaction with cells and cytokines playing an important role to be involved in the immunopathogenesis of psoriasis vulgaris